2022
DOI: 10.1001/jama.2022.13123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Remote Ischemic Conditioning vs Usual Care on Neurologic Function in Patients With Acute Moderate Ischemic Stroke

Abstract: Question: Does remote ischemic conditioning improve neurological function in patients with acute moderate ischemic stroke? Findings: In this randomized clinical trial that included 1893 participants with acute moderate ischemic stroke, excellent neurological function at 90 days in those randomized to remote ischemic conditioning compared with usual care occurred in 67.4% vs 62.0%, a difference that was statistically significant.Meaning: Although remote ischemic conditioning was associated with better neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
81
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 37 publications
(69 reference statements)
1
81
0
1
Order By: Relevance
“…It works through controlled and transient periods of subcritical ischemia to non-vital arteries ( 16 18 ), activating endogenous tissue repair mechanisms to exert neuroprotective effects, cardiovascular protection, and promote neurological recovery ( 4 , 19 , 20 ). Recently, Chen and his colleagues published the results of the Remote Ischemic Conditioning for Acute Moderate Ischemic Stroke (RICAMIS) trial, the largest randomized clinical trial to date of RIC in patients with AIS ( 21 ). This study indicated that 2 weeks of RIC in patients with acute moderate ischemic stroke within 48 h from symptom onset was associated with an increase in the odds of a favorable outcome (modified Rankin Scale [mRS] 0–1) at 90 days ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It works through controlled and transient periods of subcritical ischemia to non-vital arteries ( 16 18 ), activating endogenous tissue repair mechanisms to exert neuroprotective effects, cardiovascular protection, and promote neurological recovery ( 4 , 19 , 20 ). Recently, Chen and his colleagues published the results of the Remote Ischemic Conditioning for Acute Moderate Ischemic Stroke (RICAMIS) trial, the largest randomized clinical trial to date of RIC in patients with AIS ( 21 ). This study indicated that 2 weeks of RIC in patients with acute moderate ischemic stroke within 48 h from symptom onset was associated with an increase in the odds of a favorable outcome (modified Rankin Scale [mRS] 0–1) at 90 days ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chen and his colleagues published the results of the Remote Ischemic Conditioning for Acute Moderate Ischemic Stroke (RICAMIS) trial, the largest randomized clinical trial to date of RIC in patients with AIS ( 21 ). This study indicated that 2 weeks of RIC in patients with acute moderate ischemic stroke within 48 h from symptom onset was associated with an increase in the odds of a favorable outcome (modified Rankin Scale [mRS] 0–1) at 90 days ( 21 , 22 ). The result of this trial demonstrated that RIC training at the acute stage of ischemic stroke was feasible and improved long-term functional prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of JAMA , Chen and colleagues report the results of the Remote Ischemic Conditioning For Acute Moderate Ischemic Stroke (RICAMIS) trial, the largest randomized clinical trial to date of RIC in patients with stroke. The authors report that compared with usual care, RIC was beneficial in patients with moderate ischemic stroke (National Institutes of Health Stroke Scale [NIHSS] score, 6-16; median, 7) who did not receive tPA or mechanical thrombectomy and were treated within 48 hours of stroke (mean, 25 hours).…”
mentioning
confidence: 99%
“…In August, JAMA published (Chen et al, 2022) an open label randomized trial from China testing remote ischemic limb conditioning (RIC) in 1,893 patients with acute ischemic stroke. Supported by preclinical literature, the investigators aimed to test a new approach that they advocate is a neuroprotective strategy-inflate a cuff to both arms to cause limb ischemia.…”
mentioning
confidence: 99%